Implementation of ICT (Information Communication Technology) Based Educaplay Game to Improve Learning Comprehension of IPAS 5th Grade Students of SD Muhammadiyah Plus Malangjiwan - Pramestiya, Risma; Sukartono, (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
In the digital era, ICT media plays a crucial role in supporting education, especially in enhancing student motivation and participation. One such innovative learning tool is Educaplay, which is designed to make learning more engaging. This study aims to: 1) describe the planning process for the implementation of ICT-based Educaplay Games, 2) outline the implementation process of ICT-based Educaplay Games, 3) identify the supporting and inhibiting factors in the implementation of ICT-based Educaplay Games, and 4) propose solutions to overcome the inhibiting factors in the implementation of ICT-based Educaplay Games in grade 5 IPAS learning at SD Muhammadiyah Plus Malangjiwan. This research adopts a case study design involving the class teachers and fifth-grade students of SD Muhammadiyah Plus Malangjiwan as research subjects. Data were collected through observation, interviews, and documentation, with triangulation of sources and techniques used to ensure data validity. The data were analyzed using data reduction, data presentation, and conclusion drawing. This research contributes to the development of more engaging teaching techniques, fostering a more interactive learning experience for students. Furthermore, the findings offer guidance for schools in integrating technology into the learning process. The use of Educaplay games in IPAS learning at SD Muhammadiyah Plus Malangjiwan has proven that Educaplay is an enjoyable, highly interactive, and stimulating tool, which enhances students' enthusiasm, activity, and motivation in understanding the material.